Uropathogen Antibiotic Resistance in Adult Women Presenting to Family Physicians with Acute Uncomplicated Cystitis - Warren J McIsaac; Tony Mazzulli; Rahim Moineddin; Janet Raboud; Susan Ross (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Increasing rates of trimethoprim-sulfamethoxazole (TMP-SMX) resistance among uropathogens have raised concerns about its continued role in empirical treatment of acute uncomplicated cystitis in adult women.